Оптимальное проектирование многокомпонентных конструкций сельскохозяйственного машиностроения - Симсон, Эдуард Альфредович; Назаренко, Сергей Александрович (Харьковский национальный технический университет сельского хозяйства им. Петра Василенко, 2016)
Реальные задачи проектирования агротехники отличаются необходимостью применения комплексных моделей функционирования, сложной пространственной геометрией, большим количеством критериев и ограничений. Рассмотрены стадии оптимизации многокомпонентных конструкций агротехники: выбор комплексных многодисциплинарных математических моделей анализа функционирования; определение параметров проектирования в пространстве поиска; выбор функционалов качества (критериев цели) и ограничений оптимизируемого агрегата; определение метода оптимизации. Проанализирован многоуровневый иерархический подход. Разработаны две базовые методики анализа чувствительности и оптимизации при проведении исследования жизненного цикла многокомпонентных конструкций агротехники - от проектирования до эксплуатации и утилизации. Приведены примеры реализованных прикладных инжиниринговых разработок и проектирования изделий агротехники.

The works in optimal design of agricultural engineering have been described in this article. Short information is resulted about the basic creative stages and fundamental scientific achievements of National Technical University "Kharkiv Polytechnic Institute". The real problem of modeling agricultural machines is the need to use complex models of functioning, complex spatial geometry, a large number of criteria and functional limitations. The stages of optimization of multi-component structures of agricultural machines have been considered: the choice of mathematical analysis models; selection of design parameters of the search space; functional definition of quality (objective criteria) and restrictions optimized unit; optimization methods. Multi-level hierarchical approach is analyzed. Two basic analysis techniques of sensitivity and optimization when carrying out a research of life cycle of multicomponent constructions of an agrotechnology – from design before operation and utilization have been developed. The use of technology of "Simulation based design" is based on the application of multiple modeling by finite elements of arbitrary characteristics of loaded structures of agriculture in different production environments. Examples of the realized applicationoriented engineering development and design of products of an agrotechnology are given.
Optimal design of multi-component structures of agricultural engineering
Keywords: агротехника; оптимизация; машинно-тракторный агрегат; конечные элементы; информационные технологии; компьютерная механика; жизненный цикл; multidisciplinary optimization; machine-tractor unit; mechanics; finite element method; agricultural machines; virtual product development; mathematical modeling; digital prototyping; life cycle